Treatment of social behavior in autism through the modification of pivotal social skills. - Koegel, R I (1993)
We examined acquisition of individual social communicative behaviors and generalization across other social behaviors in 2 children with autism. The results of a multiple baseline design showed that the children's treated social behaviors improved rapidly and that there were generalized changes in untreated social behaviors. These improvements were accompanied by increases in subjective ratings of the overall appropriateness of the children's social interactions. The results suggest the possibility of identifying pivotal response classes of social communicative behavior that may facilitate the understanding of social behavior in autism as well as improve peer interactions, social integration, and social development.